Obszary aktywności członków polskich partii politycznych z perspektywy zadań partii i aspiracji jej działaczy (grassroots) - Wincławska, Maria (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
Działania członków partii politycznych w interesie ich macierzystych organizacji należą do ich najważniejszych funkcji. Z jednej strony partie nakładają na członków określone zadania i oczekują ich wypełnienia. Z drugiej strony członkowie będąc uczestnikami życia partyjnego mają swoje wyobrażenia na temat tego czego partie od nich oczekują oraz mają swoje oczekiwania wobec partii. Problem, który stawiam w tym artykule dotyczy zbieżności między: 1) postrzeganiem zadań stawianych członkom przez ich partie, 2) zadaniami rzeczywiście przez nich wykonywanymi oraz 3) oczekiwaniami żywionymi przez nich wobec partii odnośnie wypełnianych w partiach funkcji. Badaniem zostali objęci członkowie polskich partii politycznych: Prawa i Sprawiedliwości, Platformy Obywatelskiej, Nowoczesnej, Polskiego Stronnictwa Ludowego, Sojuszu Lewicy Demokratycznej i Partii Razem, którzy odpowiadali na pytania zawarte w kwestionariuszach ankiet. W wyniku badania ustalono, że postrzeganie oczekiwań partii oraz wykonywane rzeczywiście zadania na rzecz swoich ugrupowań rozmijają się z oczekiwaniami członków. Przede wszystkim nie zaspokajają one ich ambicji bycia podmiotami działań partyjnych, wpływającymi na podejmowane decyzje, a nie tylko jednostkami wykonującymi zadania instrumentalne oraz legitymizacyjne na rzecz swoich ugrupowań.

Members of political parties perform different functions within and for their organizations. Political parties impose upon their members certain tasks and expect them to fulfil them for the common good of the party. The members at the same time have their own image of what do the parties expect of them, but they also have their own expectations towards the parties. The problem I raise in this article is the concurrence of these mutual expectations and activities: (1) perceptions of the tasks the party impose on the members, (2) actual tasks that are performed by the members, and finally their (3) expectations of what forms of activities they would like to undertake within and for their parties. The research was conducted among the members of: the Law and Justice (PiS), the Civic Platform (PO), the Modern (.N), the Polish People’s Party (PSL), the Democratic Left Alliance (SLD) and the Party Together (Razem). Members of these parties filled in questionnaires. As the result of the research it can be stated that the perception of the party expectations towards the members and the tasks they actually fulfil are considerably diverged from the activities they would like to perform. Most of all, the given and performed tasks do not satisfy their ambitions as to be the subjects of the party’s activities and decisions, but only individuals who perform instrumental and legitimising functions for their organizations.
Activities of the members of Polish political parties from the perspective of the functions and aspirations of the grassroots
Keywords: członkowie partii; funkcje członków partii; oczekiwania członków wobec partii; organizacja partyjna; members of political parties; functions of the members of political parties; expectations of the members of political parties; party organization